PROGRAM EDUKASI “HOW TO BE AN IMPACTFUL YOUNGPRENEUR” PADA SISWA SMA TRI KARYA SURABAYA - Sitepu, Sri Nathasya Br; Michelle, Michelle (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2023)
The IBM Goes to School community service program is held with the aim of equipping Tri Karya High School students with skill sets that can support the creation of youngpreneurs in Indonesia. The problems faced by students are related to the tendency to have a fixed mindset and lack of courage to get out of their comfort zone. Educational program with the theme "How to Be an Impactful Youngpreneur". The educational program aims to provide a new picture and meaning about entrepreneurship to answer students' problems. The implementation method used is an educational method through presentation of material and a series of interactive activities to support the material. The results of this program include: 1) succeeded in providing encouragement to hone students' growth mindset skills, 2) succeeded in providing encouragement to step outside their comfort zone, 3) was able to motivate students to start their own businesses, 4) provided an illustration for the formation of an entrepreneurship style students of Tri Karya High School. Overall, this program has been successfully implemented and reaped a positive response through the enthusiasm and changes experienced by the students.